(untitled) (Nordic Journal of African Studies, 2005)
In this paper we discuss the problems encountered in the morphological description of verbs in those Bantu languages, which use a disjoining writing system. In one method, verb structures are first identified and concatenated by using a heuristic pre-processor, and the morphological description is based on this new writing system. In another method, the morphological description is performed directly by using the finite state tool package of Xerox. Test languages are Kwanyama and Northern Sotho. Both methods are evaluated and their limitations discussed, including the memory problems encountered in describing non-concatenative processes.